A meta-analysis on the effectiveness of Traditional Chinese Medicine Emotional Nursing in improving anxiety and depression symptoms in elderly patients - Zhao, Chunxiao; Chen, Xuelian; Zhang, Aihua; Huo, Ningya; Yu, Siyao; Lai, Lizu; Liu, Jing (Frontiers in Psychology, 2025)
BackgroundThis study used meta-analysis to explore the effectiveness of Traditional Chinese Medicine (TCM) emotional nursing intervention on the anxiety and depression of the elderly and factors that might influence this intervention, so as to provide reference for optimizing the effect of TCM emotional nursing for the elderly patients.MethodsRandomized controlled trials of TCM emotional nursing on improving anxiety and depression symptoms in elderly patients were searched from PubMed, Web of Science, Cochrane Library, Science Direct, China National Knowledge Infrastructure (CNKI), Wanfang Standards Database, and CQVIP. The Cochrane Collaboration’ s tool was adopted for assessing risk of bias of studies, and CMA 3.3 was used for statistical analysis.ResultsThirty-nine literatures and 40 studies finally met the study standards, including 4,425 patients. The results showed that TCM emotional nursing could improve the anxiety and depression symptoms of the elderly patients with a significant large effect (anxiety: g = 2.14, depression: g = 2.18). Subgroup analysis and meta-regression analysis showed that scale type, sample size and age of subjects affected the effect of intervention on anxiety. Sample size, age of subjects and course of disease affect the effect of intervention on depression.ConclusionTraditional Chinese Medicine emotional nursing can significantly improve the symptoms of anxiety and depression in the elderly. Future studies may further focus on the moderators of the Effectiveness of TCM emotional nursing intervention, and optimize the intervention plan.